The construction of persuasiveness of selfassessment- based post-completion auditing reports - Jari Huikku; Kari Lukka (Taylor & Francis, 2022)
In this study, we investigate how persuasiveness of self-assessment-based post-completion auditing (PCA) reports on capital investment is constructed. We examine what makes companies consider that information in these reports rises to an acceptable quality level. The investigation was motivated by extant agency theory (AT) informed literature suggesting that self-auditing will entail obvious risks for the quality of PCA reports in terms of data manipulation. We employed actor-network theory as our method theory. The empirical evidence of our case study came from 24 semi-structured interviews and the analysis of the construction of 22 PCA reports of strategic investments in one of the major European forest companies. We add to the capital budgeting literature by identifying and discussing the role of various conditions affecting the construction of persuasiveness of PCA reports. We maintain that the existence of three conditions (i.e. an appropriate collective process, alignment with relevant external/internal reference points, and following of formal guidance) can play a major role in facilitating the production of a persuasive PCA report. Additionally, the paper is able to make sense of the complex process of fabricating the persuasiveness of PCA reports, which would remain a black box when examined from the AT viewpoint only.